Studies of the Adsorption of SO, H and O on a CrO Surface by an Electrical Conductivity Technique - Mahmoud M. Khader; Mahmoud M. Saleh; Ahmad M. Mohammad (Adsorption Science & Technology, 1999)
Electrical conductivity measurements have been used to detect extremely small changes in the oxygen content of oxide semiconductors in contact with reducing or oxidizing gases. In continuation of previous studies, the oxygen loss of chromium oxide in H 2 and SO 2 flows, as well as the oxygen gain in an oxygen atmosphere, were studied. In SO 2 , the conductivity dropped instantaneously to minimum values due to its adsorption on adsorbed oxygen sites. The treatment of Cr 2 O 3 in SO 2 led to the elimination of chemisorbed oxygen and the covering of the surface with polymeric SO 2 . In contrast, in an H 2 flow, the conductivity of Cr 2 O 3 initially exhibited an induction period during which the value was constant. At the end of the induction period, the conductivity increased rapidly to a maximum value and then dropped sharply to a minimum. The induction period may be regarded as the time necessary to create an oxygen vacancy, the activation energy for such a process being 21.1 kJ/mol. A hydrogen molecule is then adsorbed on to the oxygen vacancy possibly as a hydride ion, and leading to the initial increase in the conductivity. The hydride ion then migrated to a chemisorbed oxygen site, where it formed a surface hydroxy group and caused a consequent decrease in the electrical conductivity. The surface then dehydroxylated due to the interaction of surface hydroxy groups with gaseous hydrogen, leaving coordinatively unsaturated surface chromium ions behind. In an oxygen flow at 400°C and above, either SO 2 or H 2 treatments led to a sharp increase in conductivity due to oxygen adsorption. In contrast, at temperatures less than 350°C, oxygen adsorption was retarded after an SO 2 flow, possibly due to the strong adsorption of a polymeric film of SO 2 . Correspondingly, after H 2 treatments, oxygen was adsorbed instantaneously at temperatures as low as 200°C, presumably because of the weak sorption of H 2 on the surface chromium ions. After discontinuing the hydrogen flow, further oxygenation caused a subsequent decrease in the conductivity, possibly due to surface hydroxylation. Hydrogen trapped in the bulk of the Cr 2 O 3 could spill over the surface and cause such a hydroxylation process.